Effect of heat treatment on oxidation resistance of magnesium alloys with additions of calcium oxide. (October 2022) - Liu, S.Y.; Liu, G.J.; Yu, C.; Lippmann, S.; Zhu, Y.F.; Jiang, Q.
Abstract: The paper investigated the effect of heat treatment on the oxidation resistance (OR) of Mg alloyed by CaO with 1, 3 and 5 wt%. After heat treatment at 400 ºC in Ar atmosphere, the increase of OR was most striking for CaO at 3 wt%. The improved OR is attributed to a uniform and dense, 50 nm thin protective MgO-CaO composite layer formed on the surface during heat treatment. The protective layer formation is largely caused by outward diffusion of Ca atoms and a gradient in the partial pressure of oxygen. Highlights: A preheating treatment was carried out for Mg-xCaO at 400 ºC in Ar inert atmosphere. The oxidation resistance was improved by the preheating especially for Mg-3CaO alloys oxidized in 0.1 MPa O2 at 400 ºC. The improvement is attributed to a protective CaO-MgO composite film formed on the surface.